Expression of cell adhesion molecule L1 in the long head of biceps tendon - Alpantaki, K.; Savvaki, M.; Karagogeos, D. (Cellular and Molecular Biology, 2010)
Several studies have proposed that the nervous system participates in nociception and tendon healing process. The neural cell adhesion molecule L1 (L1-CAM), which has an important role in neural development and nociceptive pathways, has been described in the past in the skeletal muscles and tendino-muscular junction. The role of this protein in tendon pathology is unknown. Here, we show that L1-CAM is expressed in human tendons. Samples of the long head of the biceps tendon (LHB) from six patients undergoing shoulder surgery were studied. Both Western blot and immunofluorescence revealed a strong expression pattern of L1-CAM. These L1-CAM positive cells were also Tuj1 positive, suggesting a neuronal origin. To our knowledge this is the first unequivocal evidence of the presence of L1 CAM in human tendons suggesting that it may play a role in organization of extracellular matrix and tendon pain.